Streamlining pension contributions in the people republic of China. ([Manila] Asian Development Bank, 2020)
Although the government has adopted important reforms, including lowering the employer pension contribution in March 2019, further actions are needed. Measures outlined in this policy note aim to (i) consolidate the contribution base while stabilizing the level of government subsidies to the basic pension; (ii) reform the method for determining the contribution base and achieve national pooling; and (iii) establish an interagency information exchange network.
Keywords: Social rights -- China; Sustainable development; Electronic book